Development and democracy : what have we learned and how? - Elgström, Ole, 1950-; Hydén, Göran, 1938- (Routledge/ECPR studies in European political science, 2003)
This collection confirms the robust relationship between level of economic development and democracy, but suggests that globalization is a key variable in determining the tenuous nature of this relationship.